Інтриги й колотнеча довкола Всеукраїнського музейного городка: (не)приязний професійний світ Києва 1920-х – початку 1930-х рр. - Яненко, А.С. (Сіверщина в історії України, 2020)
У статті до наукового обігу залучено інформацію про інтриги, крутійство, фальш й сцени, а між тим щиросердність, співчуття й підтримку, – емоції, що вирували у музейному житті
1920‑х – початку 1930‑х рр. й закарбувалися у листах, надісланих П.П. Курінному, очільникові Лаврського музею культів та побуту (з 1926 р. Всеукраїнського музейного городка) у Києві. Окреслено основні причини конфліктів та наслідки, до яких спричиняли
непорозуміння між співробітниками київських музеїв. Висвітлено прояви приязності, гуманності й підтримки, що так само були
притаманні інтелектуальному співтовариству. Наголошено на
перспективності залучення джерел особового походження, передовсім епістолярної спадщини, для подальшого (ре)конструювання емоційного наповнення щоденного життя представників музейної спільноти між двома світовими війнами. The article deals with information about intrigues, quarrels, hypocrisy
and showdowns, and meanwhile, sincerity, compassion, and support
– emotions that swirled in the museum life of the 1920s – early 1930s
and are imprinted in letters, which were sent to Petro Kurinnyi, Head
of the Lavra Museum of Cults and Life (since 1926 the All-Ukrainian
Museum Town) in Kyiv. Documentary evidence of Kyiv museum staffs’
emotional atmosphere is given. The addressees quite openly expressed
their feelings, shared their impressions of life situations, talked about
relationships with colleagues, and gave their subjective judgments about
persons and/or events. Various causes led to misunderstandings and
conflicts: difficult life circumstances, unsatisfactory living conditions,
health problems, incompatibility of personalities and views, paying of
old scores, subordination breaches, neglect of functional duties, flirting
with the authorities, flattery, toadyism, etc. The daily routine of the
Lavra Museum (the All-Ukrainian Museum Town) was quite stressful.
Conflicts arose in particular from the coexistence of various institutions
with diametrically different functions on the territory of the nationalized
Kyiv-Pechersk monastery, first of all, the newly established
museum institution and religious communities. The structural changes
of the museum institution in the summer and autumn of 1926 also
caused disputes. One of the most emotional events of the 1920s in the
intellectual environment was Danylo Shcherbakivskyi’s tragic death,
caused primarily by conflicts and a toxic working atmosphere at the
Taras Shevchenko All-Ukrainian Historical Museum. During the totalitarianism problems caused by the «public control» also were habitual
for museums’ life. «Conscious citizens» closely monitored the Lavra
Museum activities and played havoc with museum administration’s
nerves with newspaper libels. The letters witnessed the intensification
of dissimulations and enmities in the museum community in the early
1930s, which is entirely correlated with the Sovietization processes
intensification, the authorities’ intervention to intellectual life, and
the forced transition to the «Marxist-Leninist rails». Ideological campaigns,
ideological purges and reprisals made it easier to get back at
somebody and open ways for swindles, harassment, or revenge. Personal
conflicts partly caused work sabotage and decision-making not in
favor of museum institutions. The intense and at times dramatic museum
atmosphere, however, did not rule out humanity and sensitivity.
Difficult situations induced intellectuals to seek help from colleagues,
friends or acquaintances, appealing to understanding and hoping for
support. The messages regarding Danylo Shcherbakivskyi’s tragic death
were filled with sincere grief. Friendly relationships were also reflected
in letters of greetings, supports, joy or sympathy. Further detailed examination
of the museum staffs’ correspondence, involvement of diaries,
memoirs, as well as the documents of the Soviet repressive and controlling
bodies makes it possible to contextual studies of the specified
historical period and (re)construct the emotional filling of the everyday
life of museum community representatives between the two world wars.